Establishment and Application of Microsatellite Multiplex PCR System for Cheilinus undulatus - Fangcao Zhao; Liang Guo; Nan Zhang; Kecheng Zhu; Jingwen Yang; Baosuo Liu; Huayang Guo; Dianchang Zhang (Journal of Marine Science and Engineering, 2022)
Cheilinus undulatus is a valuable seawater economic fish with tender meat, fresh taste, and high nutritional value; however, its population is rapidly declining because of massive fishing and habitat destruction. Assessing changes in genetic diversity and inbreeding levels is a very valuable monitoring tool, and multiplex PCR has the advantages of being time-efficient and economical. Here, we selected 12 pairs of polymorphic microsatellite loci, developed two multiplex PCR amplification systems based on these microsatellites, and used them to examine 30 C. undulatus specimens. The number of alleles (Na) for the 12 microsatellite markers ranged from 2 to 8. The effective allele number (Ne) ranged from 1.724 to 4.592. The expected heterozygosity (He) and observed heterozygosity (Ho) ranged from 0.420 to 0.782 and 0.100 to 0.900, respectively. The polymorphic information content (PIC) ranged from 0.422 to 0.746, with a mean value of 0.557. 5 loci deviated from Hardy-Weinberg equilibrium (HWE, p < 0.05 after Bonferroni correction). The multiplex PCR amplification system established in this study provides a basis for germplasm identification, genetic diversity analysis, and assessment of the effects of accretion and release of C. undulatus.